SHOWCASE BODY TYPE, BEING A WOMAN AND HEALTH: SENSE PRODUCTION ON THE COVERS OF BOA FORMA MAGAZINE - Maria Teresa de Assis Campos; Mariana Silva Cecílio; Fernanda Rodrigues Penaforte (Universidade do Estado do Rio de Janeiro, 2016)
Considering the representations of beautiful, young, thin and imperfection-free bodies, idealized female bodies seem to be governed by the widespread idea in advertising campaigns that the more sculpted a body is, the happier and more confident their owners are. In this scenario, the aim of this study is to understand how feelings are produced about women and the body in the discourse produced by the covers of Boa Forma magazine. Supported by the discussion in the fields of nutrition and psychology, this study was based on qualitative research. Twelve covers (editions) were selected, printed in the year 2015. The covers underwent discursive analysis, first by enumerating the more evident aspects, and later the more thorough aspects, which led to the creation of three corpora: Embodied speeches: the ideal of beauty as an object of study; Being a woman, being a body, being an abdomen and The obese body, diets and health. There was an intrinsic relationship between diet, health and beauty, using the media strategies of persuasive connotation about the necessary precautions with the body. The allusion in the concept of good shape seems to be available to all women and linked exclusively to their merit. It could be inferred that, as an exercise of control over women's bodies, diets are designed not to work and ideal body images are produced not to be achieved, which can generate feelings of guilt, eating disorders and tensions, with consequences to the identities of subjects. Thus, the study showed the importance of awareness of naturalized "truths" we are subjected to. DOI: 10.12957/demetra.2016.22394